Numerical investigations on infilled frames and predictive formulae in the elastic regime. (1st January 2022) - Di Nino, Simona
Abstract: An in-plane finite element model of infilled frame systems is formulated. A frame–infill interface capable of transferring only normal compressive contact forces is defined. The complex phenomenology affecting these systems is explored, with a focus on the contact/separation conditions at the interface. Comparisons with previously reported experimental and numerical findings are made, and the model is validated. Parametric analyses are performed. Interpolation formulae are determined, which estimate frame–infill contact lengths and global stiffness in the elastic regime. Highlights: Contact/separation conditions take place at the frame–infill interfaces. FE model provides the most accurate predictions than literature findings. Contact lengths and stiffness are estimated by interpolation laws.